Nitrate Leaching in Californian Rice Fields: A Field‐ and Regional‐Scale Assessment. Issue 3 (1st May 2014) - Liang, X. Q.; Harter, T.; Porta, L.; van Kessel, C.; Linquist, B. A.
Abstract : Irrigated croplands can be a major source of nitrate‐N (NO3 –N) in groundwater due to leaching. In California, where high NO3 –N levels have been found in some areas of the Central Valley aquifer, the contribution from rice systems has not been determined. Nitrate leaching from rice systems was evaluated from soil cores (0–2 m), from the fate of 15 N fertilizer in replicated microplots, and from about 145 regional groundwater wells. Soil NO3 –N concentrations were ≤3.3 mg kg −1 (usually <1 mg kg −1 ) below the root zone (below 33 cm depth). In pore‐water samples, NO3 –N was observed only below the root zone during the first 2 wk after the onset of flooding in either the growing season or the winter fallow period and was always ≤8.4 mg L –1 . Fertilizer 15 N accounted for 0 to 11.8% of NO3 –N in pore‐water samples below the root zone. One year after application, based on an analysis of soil core samples, on average 2.5% of fertilizer N was recovered as 15 N below the root zone (33–100 cm), possibly due to leaching in permeable soils or via preferential flow through cracks in heavy clay soils. Based on a regional assessment, groundwater samples from wells that are located in proximity to rice fields all had measured median NO2 –N and NO3 –N levels below 1 mg L −1 . These results indicate that NO3 –N leaching from the majority of California rice systems poses little risk to groundwater under current crop management practices.